Utilisation of the site assessment energy indices for aquaculture in exposed waters: biology, technology, operations and maintenance - Heasman, Kevin G.; Sclodnick, Tyler; Goseberg, Nils; Scott, Nicholas; Chambers, Michael; Dewhurst, Tobias; Rickerich, Samuel; Føre, Heidi Moe; Buck, Bela H. (Frontiers in Aquaculture, 2024)
When moving from a very sheltered aquaculture site to a very exposed oceanic aquaculture site, the energy increases proportionally in a continuum. Lojek et al. (in review) considered the primary influential parameters (water current, wave height, wave period, wavelength and water depth) which influence the species, structure, technology, methods, and operational aspects of any aquaculture endeavour and investigated six possible indices which cover these variables. Added to advanced computer modelling, assisted by detailed and constant environmental monitoring, it may be possible to refine site selection, structure selection and design, species selection, equipment and logistic requirements and health and safety requirements. This manuscript has selected two indicative indices: Specific Exposure Energy (SEE) index and Exposure Velocity (EV) index from the potential equations provided by Lojek et al. (in review) and compared them with known operational aquaculture sites highlighting present structural capability and limitations. The two indices are also utilized to reflect on their suitability for assessing sample sites with respect to biological, technological, operational or maintenance aspects of aquaculture activities. The indices have shown themselves to be useful tools in the general assessment of the energy that will influence the species and structure selection at potential aquaculture sites. This information can help prospective fish farmers characterize their sites concisely and accurately to consultants, regulators, equipment vendors, and insurance brokers.